Effect of 𝘽𝙖𝙘𝙞𝙡𝙡𝙪𝙨 𝙡𝙞𝙘𝙝𝙚𝙣𝙞𝙛𝙤𝙧𝙢𝙞𝙨 on Growth, Survival Rate and Immune of Giant Freshwater Prawn (𝙈𝙖𝙘𝙧𝙤𝙗𝙧𝙖𝙘𝙝𝙞𝙪𝙢 𝙧𝙤𝙨𝙚𝙣𝙗𝙚𝙧𝙜𝙞𝙞) - Labaiden, Matthura; Nonwachai, Thasanee; Boonprasert, Winyoo (Burapha Science Journal, 2024)
Background and Objectives : Giant freshwater prawn are economic freshwater aquatic species. The intensive prawn culture affects on slow growth and disease outbreaks. Currently, there are biological shrimp farms using microorganism sush as Bacillus spp. for enhance shrimp growth and immune. The objective of this study is to determine effects of Bacillus licheniformis on growth survival rate and immune of Macrobrachium rosenbergii . Methodology : Prawns (size 5.23±0.007 g) were stocked in 0.52×1×0.42 meters tanks at density 13 prawns/tank (25 prawns/m2). The experiment was Completely Randomized Design (CRD) and divided in to 4 treatments. Each treatment had 3 replications. The first treatment was commercial pelleted feed (control), the 2nd, 3rd and 4th treatments were commercial pelleted feed with B. licheniformis at concentration 1, 5 and 10 g/feed 1 kilograms respectively. The growth, survival rate and immune were recorded during culture for 60 days. Main Results : Growth and survival rate of prawn in treatment 4, 3 and 2 fed with B. licheniformis were 11.71±0.29, 11.18±0.56, and 10.41±0.71 grams, respectively and significantly higher than the control group (p<0.05). For the prawn immunity, prawn fed with probiotic in treatment 4 had total hemocyte count and phagocytosis activity better than control group (p<0.05). Conclusions : Prawn fed with diet containing B. licheniformis at concentration 10 g/feed 1 kilograms was able to enhance growth, survival rates and immune than the control group.